The Proposal of the Measurement Tool on the Investigation of Lower Secondary School Pupils‘ Attitudes toward Biology - Kubiatko, Milan; Vlčková, Jana (Scientia in educatione, 2020)
The study is focused on lower secondary school pupils’ attitudes toward biology as a school subject and describes the development of our own measurement tool. The 5- point questionnaire of Likert type was used as a measurement tool. It consists of 52 items. The pilot study was carried out with 75 pupils from all grades of lower secondary school. The final version was determined on the basis of analysis results, which consisted of 39 items. In addition, the influence of gender, class, residence and favorite subject on the pupils’ attitudes toward biology was analyzed.